Three techniques for the fabrication of high precision, mm-sized metal components based on two-photon lithography, applied for manufacturing horn antennas for THz transceivers. (31st January 2018) - Standaert, Alexander; Brancato, Luigi; Lips, Bram; Ceyssens, Frederik; Puers, Robert; Reynaert, Patrick
Abstract: This paper proposes a novel packaging solution which integrates micro-machined 3D horn antennas with millimeter-wave and THz tranceivers. This packaging solution is shown to be a valid competitor to existing technologies like metallic split-block waveguides and low temperature cofired ceramics. Three different fabrication methods based on two-photon lithography are presented to form the horn antennas. The first uses two-photon lithography to form the bulk of the antenna. This structure is then metalised through physical vapor deposition (PVD) and copper plating. The second fabrication method makes use of a soft polydimethylsiloxane (PDMS) mold to easily replicate structures and the third method forms the horn antenna through electroforming. A prototype is accurately positioned on top of a 400 GHz 28 nm CMOS transmitter and glued in place with epoxy, thus providing a fully packaged solution. Measurement results show a 12 dB increase in the antenna gain when using the packaged solution. The fabrication processes are not limited to horn antennas alone and can be used to form a wide range of mm-sized metal components.